Governance Of The Development Of Asmara Garden Agrotourism In East Bulotalangi Village East Bulango District Bone Bolango Regency - Bilatula, Sitti Nadia; Igirisa, Irawaty; Hamim, Udin (Public Policy Journal, 2025)
This study aims to determine (1) the Governance of the Developmentof Asmara Garden Agrotourism in Bulotalangi Timur Village, Bulango TimurDistrict, Bone Bolango Regency, which is reviewed from the planning,implementation and evaluation. (2) Factors that determine the development ofAsmara Garden Agrotourism Development in Bulotalangi Timur Village, BulangoTimur District, Bone Bolango Regency, which is seen from the attractions,accessibility and amenities. This study uses a qualitative approach method with aqualitative descriptive research type, and uses data collection techniques withobservation, interviews and documentation. Based on the results of the researchconducted, (1) Governance in the development of Asmara Garden agrotourismwhich includes planning, implementation, and evaluation has been runningoptimally. However, it has not been running fully, such as the lack of communityparticipation and involvement in managing Asmara Garden at this time. (2) Thefactors that determine the development of Asmara Garden agrotourism, namelyattractions, accessibility and amenities, are quite adequate. However, there arestill some that have not been fulfilled, such as attractions that have begun todecrease and amenities that are damaged and the lack of other supportingfacilities.